Proceedings of the 16th ACM International Conference on Modeling, Analysis &Amp; Simulation of Wireless and Mobile Systems 2013
DOI: 10.1145/2507924.2507998
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic content distribution

Abstract: Epidemic content dissemination has been proposed as an approach to mitigate frequent link disruptions and support content-centric information dissemination in opportunistic networks. Stochastic modeling is a common method to evaluate performance of epidemic dissemination schemes. The models introduce assumptions which, on one hand make them analytically tractable, while on the other, ignore attested characteristics of human mobility. In this paper, we investigate the fitness and limitations of an analytical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…These studies have demonstrated the versatility of BT-based collected data for recognizing social patterns, inferring social relationships, creating networking structures [1]- [6] or even influencing mental health [7]. In addition, BT data has been leveraged for context-oriented opportunistic networking applications and epidemic modeling [28], [29], [31]. The outcomes of the social networks inference have been applied to many domains for providing improved networking services [2], designing communication overhead algorithms [4], or modeling social distance measures [28].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated the versatility of BT-based collected data for recognizing social patterns, inferring social relationships, creating networking structures [1]- [6] or even influencing mental health [7]. In addition, BT data has been leveraged for context-oriented opportunistic networking applications and epidemic modeling [28], [29], [31]. The outcomes of the social networks inference have been applied to many domains for providing improved networking services [2], designing communication overhead algorithms [4], or modeling social distance measures [28].…”
Section: Introductionmentioning
confidence: 99%